Efficacy of Different Pesticides against Fall Armyworm (Spodoptera frugiperda (J.E. Smith) Lepidoptera: Noctuidae) under Laboratory Conditions in Rupandehi, Nepal - Dipak Khanal; Dipesh Subedi; Gaurave Banjade; Manila Lamichhane; Sapana Shrestha; Prashant Chaudhary (International Journal of Agronomy)
The fall armyworm (FAW), Spodoptera frugiperda, is a highly destructive pest recently reported in various Asian countries and originated in the subtropical regions of America. It was first recorded in Nepal on May 9, 2019. This invasive species poses a significant threat to maize production because it can undergo multiple generations, migrate, and feed on a wide range of host plants. A laboratory study was conducted with 3 categories of pesticides: conventional, newer, and bio-rational. The study focused on evaluating the efficacy of these pesticides on the third-instar larvae of S. frugiperda. The treatments included (1) newer chemical pesticides: spinosad 45% suspension concentrate (SC) (Tracer 1 ml/3 L of water), spinetoram 11.7% SC (Delegate 0.5 ml/L of water), chlorantraniliprole 18.5% SC (Allcora 1 ml/2.5 L of water), emamectin benzoate 5.7% water dispersible granules (WDG) (top killer 1 g/2.5 L), (2) conventional pesticide: chlorpyrifos 50% EC (Predator 2 ml/L), and (3) bio-rational pesticides: Bacillus thuringiensis var kurstaki 0.5% wettable powder (WP) (Maharashtra 2gm/L), Metarhizium anisopliae 1.0% WP (Kalichakra 5 ml/L), Beauveria bassiana 2% AS (DamanL 5 ml/L), Azadirachta indica 4.5% (Neemix 5 ml/L), Syzygium aromaticum 100% v/v (Kanti herbal Clove oil 3 ml/L), and spinosad 45% SC (Tracer 0.3 ml/L). Fresh maize leaves were treated using the leaf dip method and then fed to 3rd instar larvae of FAW. The results revealed that spinetoram and spinosad caused 100% larval mortality within the first 24 hours after treatment. Similarly, spinosad (99.99%) and clove oil (76.64%) were the most effective bio-rational pesticides followed by B. bassiana and B. thuringiensis. The newer and bio-rational pesticides that showed high efficacy could be suggested for further study in farmers’ fields. They could be recommended for testing as a component of integrated pest management for effective management of FAW in Nepal.